2012
DOI: 10.1111/j.1365-2958.2012.08115.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of thiol‐oxidative stress responses regulated by SigR orthologues in actinomycetes

Abstract: Summary Numerous thiol-reactive compounds cause oxidative stress where cells counteract by activation of survival strategies regulated by thiol-based sensors. In Streptomyces coelicolor, a model actinomycete, a sigma/antisigma pair SigR/RsrA controls the response to thiol-oxidative stress. To unravel its full physiological functions, chromatin immuno-precipitation combined with sequence and transcript analyses were employed to identify 108 SigR target genes in S. coelicolor and to predict orthologous regulons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 64 publications
2
93
0
Order By: Relevance
“…In this context, it should be noted that the suf operon encoding proteins involved in Fe-S cluster biosynthesis is also included in the H regulon (14). Induction of genes for biosynthesis of stresssensitive cofactors, including the Fe-S cluster, lipoic acid, coenzyme A (CoA), and NAD, and of those for enzymes carrying the cofactors by alternative sigma factors have been known (30,56).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it should be noted that the suf operon encoding proteins involved in Fe-S cluster biosynthesis is also included in the H regulon (14). Induction of genes for biosynthesis of stresssensitive cofactors, including the Fe-S cluster, lipoic acid, coenzyme A (CoA), and NAD, and of those for enzymes carrying the cofactors by alternative sigma factors have been known (30,56).…”
Section: Resultsmentioning
confidence: 99%
“…These findings provide new insights into the functions of H in the stress response and in the structure of the transcriptional regulatory network in C. glutamicum. Moreover, the C. glutamicum H regulon defined here has some components in common with the S. coelicolor R regulon, which has been recently identified by ChIP-chip analysis (30), indicating functional conservation of the H orthologs among Actinomycetales.…”
mentioning
confidence: 99%
“…s R orthologues and their predicted regulons are well conserved in actinomycetes (Kim et al, 2012). In S. coelicolor, the activity of s R is regulated by anti-s factor RsrA, which is inactivated by formation of disulphide bonds and releases s R to transcribe its regulon under oxidative stress (Bae et al, 2004;Kang et al, 1999;Paget et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The sigR gene in S. avermitilis also has a standard s R -dependent promoter (GGAAT-N 18 -GTT; p2) (Kim et al, 2012). Our 59-RACE analysis of sigR transcripts revealed that another promoter (p1), located 163 nt downstream of p2, was the constitutive promoter in the absence of stress (Fig.…”
Section: Expression Of Ahpcd Is Positively Regulated By Oxyrmentioning
confidence: 99%
See 1 more Smart Citation